2014
DOI: 10.1371/journal.pone.0095019
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship between Reduced Nucleus Accumbens Shell and Enhanced Lateral Hypothalamic Orexin Neuronal Activation in Long-Term Fructose Bingeing Behavior

Abstract: Fructose accounts for 10% of daily calories in the American diet. Fructose, but not glucose, given intracerebroventricularly stimulates homeostatic feeding mechanisms within the hypothalamus; however, little is known about how fructose affects hedonic feeding centers. Repeated ingestion of sucrose, a disaccharide of fructose and glucose, increases neuronal activity in hedonic centers, the nucleus accumbens (NAc) shell and core, but not the hypothalamus. Rats given glucose in the intermittent access model (IAM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 76 publications
5
32
0
Order By: Relevance
“…A role for the OX1R in mediating intake of palatable food is supported by the findings that systemic injection of the OX1R antagonist, SB-334867, reduces operant responding for both sucrose and saccharin pellets, in a minimal work paradigm with a fixed ratio 1 schedule (Cason & Aston-Jones, 2013a, 2013b, 2014). This antagonist also suppresses binge-like intake of sucrose, saccharin, and fructose solutions under an intermittent-access home cage drinking paradigm (Alcaraz-Iborra, Carvajal, Lerma-Cabrera, Valor, & Cubero, 2014; Rorabaugh, Stratford, & Zahniser, 2014) and reduces intake of a high-fat diet under both ad libitum and limited-access feeding paradigms (Choi, Davis, Fitzgerald, & Benoit, 2010; Valdivia, Patrone, Reynaldo, & Perello, 2014; White et al, 2005). Other OX1R antagonists similarly reduce intake of sweet-fat foods whether under ad libitum or intermittent-access feeding paradigms (Piccoli et al, 2012; Steiner, Sciarretta, Pasquali, & Jenck, 2013).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…A role for the OX1R in mediating intake of palatable food is supported by the findings that systemic injection of the OX1R antagonist, SB-334867, reduces operant responding for both sucrose and saccharin pellets, in a minimal work paradigm with a fixed ratio 1 schedule (Cason & Aston-Jones, 2013a, 2013b, 2014). This antagonist also suppresses binge-like intake of sucrose, saccharin, and fructose solutions under an intermittent-access home cage drinking paradigm (Alcaraz-Iborra, Carvajal, Lerma-Cabrera, Valor, & Cubero, 2014; Rorabaugh, Stratford, & Zahniser, 2014) and reduces intake of a high-fat diet under both ad libitum and limited-access feeding paradigms (Choi, Davis, Fitzgerald, & Benoit, 2010; Valdivia, Patrone, Reynaldo, & Perello, 2014; White et al, 2005). Other OX1R antagonists similarly reduce intake of sweet-fat foods whether under ad libitum or intermittent-access feeding paradigms (Piccoli et al, 2012; Steiner, Sciarretta, Pasquali, & Jenck, 2013).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…Rats were singly housed with food (Teklad 2020X chow: 3.1 kcal/g, 24% protein, 16% fat, 60% carbohydrate; Harlan Laboratories, Denver, CO) and water available ad libitum for 5 days prior to commencing experiments. Rats were subsequently tested using the sugar bingeing model, as previously described (Avena et al, 2006a; Rorabaugh et al, 2014). At the onset of the experiment, rats continued to have 24-h access to an ad libitum water bottle but were cycled between 12 h of food deprivation and 12 h of access to chow and a second intermittent bottle that contained water (control; n=10), 8% sucrose, 8% glucose, or 8% fructose solution (0.29 kcal/mL; n=10/group).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, sucrose-bingeing rats show some of the neurochemical signs of DA hypersensitivity including elevated extracellular DA levels in response to sucrose intake, decreased DA D2 receptor (D2R) levels and increased DA transporter levels within the nucleus accumbens (NAc) (Bello et al, 2002; 2003; Rada et al, 2005; Avena et al, 2006b). Glucose-bingeing, but not fructose-bingeing, rats also display reduced D2R levels within the NAc (Colantuoni et al, 2001; Rorabaugh et al, 2014). A history of sucrose bingeing enhances locomotor responses to cocaine; however, whether bingeing on sucrose, or its components glucose and fructose, similarly alters the rewarding properties of cocaine has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OX antagonist SB-334867 inhibited the expression of conditioned place preference to high fat food when administered into the fourth ventricle (Kay et al, 2014) and decreased fructose consumption by rats in an Intermittent Access Model (IAM) that triggers binge-like consumption (Rorabaugh et al, 2014). A recent study showed that inhibiting the LH-VTA pathway reduces compulsive sucrose seeking but not food consumption in hungry mice, in a partial Reinforcement Sucrose-Retrieval Task (Nieh et al, 2015).…”
Section: The Orexin Systemmentioning
confidence: 99%